Les Ouïghours en Syrie - Dilnur Reyhan (Revue des Mondes Musulmans et de la Méditerranée)
Since the onset of the war in Syria, and particularly since the emergence of the Islamic State (ISIS or Daesh), we have witnessed the expansion of IS ranks through a highly effective recruitment. Combatants from almost of countries, including China, have joined IS. The majority of Uyghur combatants have left China to join, the Turkestan Islamic Party (TIP) while others have joined IS since late 2014. Most of them were forced into exile in Turkey via Malaysia and Thailand following the intensification of Chinese repression against them, and the Chinese operations in Pakistan against the TIP fighters led to last to leave Pakistan for Syria. The most religious of these migrants are recruited by the Turkish networks, sympathizers of the TIP, while a minority is enlisted by Daesh. How are these two movements different? If the Uyghur Daeshists reject any nationalist ideology, the Uyghurs of the TIP defend a national cause and initially aim at the independence of the Uyghur region. However, in the facts, this population represents only part of this movement which includes more and more other Central Asian Turks. Indeed, the ideology of TIP has evolved over time, no longer targeting the only Uyghur cause, but the creation of a Turkic and Islamic Central Asian nation. In this context, Uyghur presence in Syria could be explained by their need to gain military experience to fight China. Only the analysis of the modes of communication and the forms of propaganda not only of the Chinese authorities but also from the different jihadist movements that we studied, as well as the analysis of the relations that each one has with the Uyghur organizations of the diaspora allows to understand in depth the current geopolitical stakes.